ANALISIS PERUBAHAN LUAS MANGROVE BERDASARKAN CITRA SATELIT IKONOS TAHUN 2004 DAN 2010 DI KECAMATAN MLONGGO, TAHUNAN DAN KEDUNG KABUPATEN JEPARA JAWA TENGAH - Karyono, Afirman; Pribadi, Rudhi; Helmi, Muhammad (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Mangrove as one of coastal ecosystem has plenty of role on coastal stability, but the current condition even though of mangroves ecosystem is Java, including Jepara destructed by many reasons mostly human activities such as. Conversion of mangrove forests to ponds, settlements and illegal logging. Rehabilitation was conducted in some places. therefore, there is a need of review the changes. The purpose of this study to determine the mangrove area changes based on IKONOS satellite imagery of 2004 and 2010 in the District Mlonggo, Tahunan and Kedung, Jepara. Descriptive method is used to describe the state of research areas by comparing the field data and interpretation process. Satellite images have been digitized in overlay to know the changes at mangrove area. Ground check was conducted the field using the quadratic sampling plots of 10m x 10m to for tree, 5m x 5m for sapling and 1m x 1m for seedling. The results were increate that the between period of 2004 to 2010. However, the mangrove area increased 5,959 ha and reduced 5,294 ha and so there was in general 0.665 ha increased. The total area at mangrove in 2004 38,098 ha and in 2010 was variously 37,444. There were at least 20 species in the research area and Rhizophora sp was the most dominant species.